The relationship and problems of gated community with strata title in Johor Bahru - Nurul Faratihah Ibrahim, 1990-; Md. Nor Kamarudin, supervisor; Fakulti Geoinformasi dan Harta Tanah (2013)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2013